Mechatronic device for the roses cultivation and harvest - Vásquez Falcony , Christian Renán; Achina, Edison Javier; Tobar Subía, Luz María (I+ T+ C- Research, Technology and Science, 2019)
The research project presents the development of a mechatronic device for the cultivation and harvest of roses, with the aim to preventing occupational diseases such as tendonitis, carpal tunnel syndrome and joint problems in people working in the flower industry in the cultivation area due to the continuous handling of mechanical scissors. It starts with an ergonomic analysis using the JSI method for jobs, then design parameters are defined based on research carried out to the force required for the cutting of stems of the roses, as well as ergonomic data that limit the geometry of the device, subsequently evaluates the operation of similar electric scissors used for the cultivation of vines and fruit trees to define the mechanical and control system of the mechatronic device. Finally, a different control system with infrared sensors is proposed to determine the position of the blade instead of limit switches. It also has a safety system that integrates with leather gloves that stop the operation of the blade, avoiding cuts or amputations of the fingers. The functioning tests were carried out in plantations of different species of roses, validating the design and solving the problem for which it was designed.